UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN SARANA DAN PRASARANAPENDIDIKAN DI TAMAN KANAK-KANAK KASIH IBU KAMPUNG TIUH BALAK KECAMATAN BARADATU KABUPATEN WAY KANAN TAHUN PELAJARAN 2017/2018 - Rusyati Prihatin (Tadzkirah : Jurnal Pendidikan Dasar, 2020)
Early childhood is the right time to do education. At this age children experience extraordinary growth and development processes. Children do not have a lot of negative influences from outside or their environment, in order to realize optimal development and growth, adequate facilities and infrastructure are needed. The formulation of this research problem is how the principal's efforts in improving educational facilities and infrastructure. This study aims to determine how the efforts of school principals in improving educational facilities and infrastructure in Kasih Ibu Kindergarten. This research is a descriptive study using a qualitative approach. Data collection methods used in this study are the method of observation, interviews and documentation. The source of the information was the Principal and the teacher at the Kindergarten of Charity Mother Tiuh Balak village. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. Based on the results of the study it can be concluded that: the facilities and infrastructure in the Kasih Ibu Kindergarten are still inadequate, the efforts of school principals in improving educational facilities namely by submitting committee and student guardian proposals, maintenance of facilities and infrastructure, providing motivation to the board of teachers to develop knowledge higher knowledge and provide opportunities for teachers to continue their education, develop more creative teachers. In addition to making efforts for teachers, school principals also provide motivation to children. The facilities and infrastructure that are prioritized to be developed by the school principal is APE (educational play equipment) because the play equipment is very beneficial for developing the mindset of children to help children discover new things. Problems in improving facilities and infrastructure, namely funding and kindergarten teachers who are still passive to try new things, especially in terms of making instructional media, writer's advice We recommend that teachers must have a high curiosity, especially in terms of their activities as educators, obtained from teacher information and knowledge- other teachers who are more experienced in teaching early childhood. teachers can also add knowledge by continuing their education to a higher level, for example S1 PAUD / PGPAUD.